2019
DOI: 10.1080/13696998.2019.1569446
|View full text |Cite
|
Sign up to set email alerts
|

Cohort versus patient level simulation for the economic evaluation of single versus combination immuno-oncology therapies in metastatic melanoma

Abstract: Background: Model structure, despite being a key source of uncertainty in economic evaluations, is often not treated as a priority for model development. In oncology, partitioned survival models (PSMs) and Markov models, both types of cohort model, are commonly used, but patient responses to newer immuno-oncology (I-O) agents suggest that more innovative model frameworks should be explored. Objective: A discussion of the theoretical pros and cons of cohort level vs patient level simulation (PLS) models provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(60 reference statements)
1
12
0
Order By: Relevance
“…Clinical endpoints of PFS, OS and BOR and common economic outcomes of LYs, QALYs and costs were considered in the evaluation. 10 The modelled outcomes for OS and PFS with the Regimen were more closely comparable with the reported trial endpoints than those in the ipilimumab arm over 4 years. This is driven by the best fits from the survival analysis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Clinical endpoints of PFS, OS and BOR and common economic outcomes of LYs, QALYs and costs were considered in the evaluation. 10 The modelled outcomes for OS and PFS with the Regimen were more closely comparable with the reported trial endpoints than those in the ipilimumab arm over 4 years. This is driven by the best fits from the survival analysis.…”
Section: Discussionsupporting
confidence: 58%
“…5 As part of an ongoing investigation into innovative economic modelling approaches, this paper complements previous studies on the extrapolation of clinical benefit beyond the clinical trial period 7 and a comparison of cohort models 8 with a patient level simulation (PLS). 10 Throughout the research, the case study of malignant melanoma has been used as it is the condition in which the longest follow-up trial data in I-O is available (with ipilimumab). 11 The current study builds particularly on Gibson et al (2018) who compared a 3-state PSM and extensions thereof with a Markov model and found that the PSM-based approaches generated results more closely comparable with existing trial data endpoints than the Markov model, 8 as expected given the way in which clinical data was reported.…”
Section: Introductionmentioning
confidence: 99%
“…decision trees, state-transition models, patient simulations) which should theoretically yield the same conclusion about the cost effectiveness of an intervention, however, due to the diverging use of data and assumptions made results are likely to differ. For example, in oncology, published examples have demonstrated that different model structures estimate different durations spent in key health states, impacting cost-effectiveness results [8][9][10][11][12]. Despite this, in the same disease area, justification for the choice of model structure is often minimal [13].…”
Section: Structural and Methodologicalmentioning
confidence: 99%
“…Again, advances are made with the trend towards more patient level modeling as compared to cohort-based models. Although in several situations and conditions the patient level approach might not contribute much to the final result and assessment as compared to cohort based models, in the case of immune-oncology, Gibson et al 4 show that the patient level approach does much better reflect heterogeneity in treatment response, leading to a more valid and reliable estimate of future QALYs.…”
Section: Editorialmentioning
confidence: 99%